2012
DOI: 10.7150/ijms.3467
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Antithyroid Antibody and Pregnancy Outcome following in Vitro Fertilization and Embryo Transfer

Abstract: Objective: To investigate the impact of antithyroid antibody on pregnancy outcome following the in vitro fertilization and embryo transfer (IVF-ET).Methods: A total of 90 patients (156 cycles) positive for antithyroid antibody (ATA+ group) and 676 infertile women (1062 cycles) negative for antithyroid antibody (ATA- group) undergoing IVF/ICSI from August 2009 to August 2010 were retrospectively analyzed.Results: There was no significant difference in the days of ovarian stimulation, total gonadotropin dose, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 21 publications
(32 reference statements)
9
77
1
3
Order By: Relevance
“…However, the authors did not investigate the prevalence of TAI in their cohort (24). Moreover, the presence of Tg-Abs may be involved in miscarriage independently from their effect on thyroid hormone function (11,25). The association between Tg-Abs and serum TSH levels did not result from differences in age, BMI, and smoking habits according to our multivariable analysis.…”
Section: Discussionmentioning
confidence: 77%
“…However, the authors did not investigate the prevalence of TAI in their cohort (24). Moreover, the presence of Tg-Abs may be involved in miscarriage independently from their effect on thyroid hormone function (11,25). The association between Tg-Abs and serum TSH levels did not result from differences in age, BMI, and smoking habits according to our multivariable analysis.…”
Section: Discussionmentioning
confidence: 77%
“…Cette pré valence est augmenté e chez les couples où une cause fé minine a é té identifié e comme l'anovulation, un syndrome des ovaires polykystiques ou encore une endomé triose [73]. Chez les patientes en cours de FIV, plusieurs é tudes ont montré que la pré sence d'anti-TPO chez des patientes euthyroïdiennes é tait un facteur dé lé tè re pour la grossesse, entraînant un sur-risque de FCS (RR = 1,99 ; IC : 1,42-2,80) [74,75].…”
Section: Succe`s Apre`s Ampunclassified
“…10 A close result has been reported in a retrospective study by Zhong et al, who found a reduced fertilization, implantation, and pregnancy rate, as well as an increased abortion rate in infertile women positive for anti-thyroid antibodies undergoing IVF. 11 It is well known that autoimmunity plays an important role in reproductive failure and some auto-Ab, in particular antiphospholipid antibodies (APL), are significantly associated with infertility. [12][13][14] More recently other auto-Ab, namely antibodies against laminin-1 (LN-1), have been associated with reproductive failure.…”
Section: Introductionmentioning
confidence: 99%